2016
DOI: 10.1093/jjco/hyw144
|View full text |Cite
|
Sign up to set email alerts
|

Respiration-gated fast-rescanning carbon-ion radiotherapy

Abstract: Phase-controlled rescanning of the carbon-ion beam offers fast and precise dose application with decreased irradiation of normal tissue. However, organ movement with respiration remains a unique challenge. Technological development has enabled the simultaneous application of beamenergy-modulated markerless phase-controlled rescanning with respiration gating, allowing scanning treatment of respiration-mobile tumors with carbon. A total of 10 patients with tumors in the liver or lung were treated in a feasibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Recently, for the purpose of dose reduction to organs at risk, scanning irradiation with respiratory gating has been started at NIRS. 32,33 The current study showed a favorable local-control rate in patients with HCC similar to the findings of previous studies on particle therapy, [11][12][13]29,31 and there were no significant differences in local failure according to tumor characteristics such as the size or stage before CIRT; this is similar to what has been reported previously. 29 This study revealed no significant differences in local failure between the 38 cases with a tumor size > 50 mm (3-and 5-year local-control rates of 88.5% and 88.5%, respectively), who might have been ineligible for liver transplantation, and the 39 cases with a tumor size 30 mm (3-and 5-year localcontrol rates of 97.1% and 91.0%, respectively).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Recently, for the purpose of dose reduction to organs at risk, scanning irradiation with respiratory gating has been started at NIRS. 32,33 The current study showed a favorable local-control rate in patients with HCC similar to the findings of previous studies on particle therapy, [11][12][13]29,31 and there were no significant differences in local failure according to tumor characteristics such as the size or stage before CIRT; this is similar to what has been reported previously. 29 This study revealed no significant differences in local failure between the 38 cases with a tumor size > 50 mm (3-and 5-year local-control rates of 88.5% and 88.5%, respectively), who might have been ineligible for liver transplantation, and the 39 cases with a tumor size 30 mm (3-and 5-year localcontrol rates of 97.1% and 91.0%, respectively).…”
Section: Discussionsupporting
confidence: 90%
“…Recently, for the purpose of dose reduction to organs at risk, scanning irradiation with respiratory gating has been started at NIRS 32, 33…”
Section: Discussionmentioning
confidence: 99%
“…However, if patient breathing pattern were monitored and proton beam delivery could be correlated to patient breathing, motion mitigation could be achieved more efficiently, in that one could now “assign” the spots to be delivered to a certain phase, instead of counting on the spots to “arrive” at those phases. Investigation on fast beam delivery with patient motion monitor has been conducted by several groups but is outside the scope of the current study. Another limitation of the study is that we assumed the patient′s position and breathing pattern remained the same as that of the 4DCT throughout treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In this technology, the position of the moving tumor can be calculated in real time using X-ray fluoroscopy (with the use of X-ray sources and dynamic flat panel detectors in the treatment room), and the scanning beam is “on” only when the center of mass of the tumor relocates to a predefined area in accordance with the respiratory cycle. In March 2015, the NIRS treated the first lung cancer patient using respiratory-gated fast rescanning CIRT [ 36 ]. Excellent reviews of the NIRS pencil beam scanning system [ 31 ] and motion management technologies [ 37 ] have been recently published and are worth reading for physicians or physicists interested in a more detailed explanation.…”
Section: Treatment Deliverymentioning
confidence: 99%